PENGARUH LUAS PANEN DAN PRODUKTIVITAS PADI TERHADAP PRODUKSI PADI DI PROVINSI KEPULAUAN BANGKA BELITUNG TAHUN 2018-2024 - Khoirun Laili Nur Amaliah; Alfio Raldo; Arini Fitria; Bagastama Iqbalil Fathir; Elyas Kustiawan; Ridho Akbar (MATHunesa: Jurnal Ilmiah Matematika, 2026)
Food security is one of the important issues in national development. In Indonesia, rice plays a role as the main commodity providing rice for the Indonesian people. Rice production in the Bangka Belitung Islands Province has shown a positive trend over the past few years. This study aims to analyze the effect of harvested area and productivity on rice production in the Bangka Belitung Islands Province. The data used are panel data of districts/cities in the Bangka Belitung Islands Province with a monthly period. The analysis method used is panel data regression with the help of EViews software. Based on the results of the Chow, Hausman, and Lagrange (LM) multiplier tests, the best model obtained is a random effects model with an estimated result of . The coefficient of determination (R²) value of 0.925579 indicates that 92.56% of the variation in rice production can be explained by harvested area and productivity, while the remaining 7.44% is explained by other variables outside the model. These results confirm that harvested area and productivity play an important role in increasing rice production in Bangka Belitung and can be a reference for local governments in formulating policies to improve food security. Keywords: Harvested Area, Rice Production, Productivity, Random Effect, Panel Data Regression.